Synthesis and characterization of magnetic properties of hard/soft nanocomposite permanent magnets - Mohd Saiden, Norlaily; Jalani, Noor Ariffuddin; Abdullah, Hartini; Ahmad, Aisyah Rahhiah; Azmi, Mohd Firdaus; Ismail, Ismayadi; Hashim, Mansor; Saion, Elias (2017)
We report on an investigation of the magnetic properties of nanocomposite ferrite via different technique. Magnetic hard and soft ferrite, SrFe12O19/ Ni0.5Zn0.5Fe2O4 nanocomposites with mass ratio 4:1 were synthesised by using the mechanical alloying (750 rpm) method, physical mixing and high energy ball milling method. The nanocomposite ferrite was calcined at different temperatures from 500°C to 800°C to study the effect of calcination temperature on the magnetic properties of nanocomposite ferrite. The X-Ray Diffraction (XRD) result shows the double phase SrFe12O19 and Ni0.5Zn0.5Fe2O4 existed. The Transmission Electron Microscopy (TEM) image shows the particlesize is agglomerated, due to the attractive force. The magnetisation measurement was obtained at room temperature by using a Vibrating Sample Magnetometer (VSM). For mixing by mechanical alloying, nanocomposite ferrite at 800°C gives the larger value of magnetisation, Ms 46 emu/g which is higher than the Ms of a single phase of SrFe12O19, 37 emu/g. The remanence ratio, Mr/Ms of nanocomposite ferrite at 800°C gives the value more than 0.5, this proves that the exchange coupling exists with the higher value of Ms. For physical mixing, the highest magnetisation obtains are 51 emu/g at a temperature of 750°C. From this simple technique, we are able to attain good magnetic properties of nanocomposite ferrite nanoparticles with a particle size below 50 nm.